2013
DOI: 10.1080/00949655.2011.602679
|View full text |Cite
|
Sign up to set email alerts
|

Detection of outliers in simple circular regression models using the mean circular error statistic

Abstract: The investigation on the identification of outliers in linear regression models can be extended to those for circular regression case. In this paper, we propose a new numerical statistic called mean circular error to identify possible outliers in circular regression models by using a row deletion approach. Through intensive simulation studies, the cut-off points of the statistic are obtained and its power of performance investigated. It is found that the performance improves as the concentration parameter of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 12 publications
(18 reference statements)
0
10
0
Order By: Relevance
“…In 2013 the first version of the package isocirc was presented (Barragán et al, 2013), making available functions to perform constrained inference using isotonic regression (Rueda, Fernández, and Peddada, 2009;Fernàndez, Rueda, and Peddada, 2011). The CircOutlier (Ghazanfarihesari and Mashhad, 2016) collects functions to detect outliers in circular-circular regression as proposed in Abuzaid, Hussin, and Mohamed (2013). More recent is the Directional package (Tsagris et al, 2018), mostly linked to the textbook by Mardia and Jupp (1999).…”
Section: Existing Software For Circular and Directional Datamentioning
confidence: 99%
“…In 2013 the first version of the package isocirc was presented (Barragán et al, 2013), making available functions to perform constrained inference using isotonic regression (Rueda, Fernández, and Peddada, 2009;Fernàndez, Rueda, and Peddada, 2011). The CircOutlier (Ghazanfarihesari and Mashhad, 2016) collects functions to detect outliers in circular-circular regression as proposed in Abuzaid, Hussin, and Mohamed (2013). More recent is the Directional package (Tsagris et al, 2018), mostly linked to the textbook by Mardia and Jupp (1999).…”
Section: Existing Software For Circular and Directional Datamentioning
confidence: 99%
“…Abuzaid et al [ 12 ] and Ibrahim et al [ 13 ] explored the problem on two types of circular regression models by observing the effect of removing one observation on the covariance matrix. Further, Abuzaid et al [ 14 ] proposed a residual measure using a cosine function to detect outliers in a linear circular regression model, where the relationship between the dependent and independent variables is strictly linear (see [ 10 ]). In this paper, we propose a new summary measure for the purpose of detecting outliers in terms of a simple measure of circular distance in DM circular regression model.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, only few studies of outliers in circular regression can be found in the literature. Abuzaid et al (2013Abuzaid et al ( , 2011 and Ibrahim et al (2013) explored the problem in two types of circular regression model using row deletion approach while Hussin et al (2010) discussed the detection of influential observation in a linear functional relationship model for circular data.…”
Section: Introductionmentioning
confidence: 99%